Synthesis and characterization of a polystyrene-type polymer bearing a cyclic perfluoroalkylene group. (16th January 2023) - Hisa, Tatsuro; Kanno, Yasunori; Shirai, Tomohiro; Oshiki, Toshiyuki; Mizuhata, Yoshiyuki; Tokitoh, Norihiro; Fukumoto, Hiroki; Agou, Tomohiro
Abstract: Perfluoroalkyl-containing aromatic compounds are predicted to have fascinating material properties. In this work, a styrene derivative bearing a cyclic perfluoroalkylene group, –(CF2 )4 –, was synthesized and polymerized to afford the corresponding polymer. The styrene derivative was obtained via the Ullmann coupling of I–(CF2 )4 –I with 3′-bromo-4′-iodoacetophenone, NaBH4 reduction of the ketone moiety, and dehydration using P4 O10 . Free-radical polymerization (FRP) of the styrene derivative afforded polymer with number-average molecular weight ( M n ) and dispersity index (DI) of 1.1 × 10 4 and 3.1, respectively. The thermal stability of the synthesized polymer ( T d10% 359 °C, T g 149 °C) was greater than the previously reported n -C4 F9 -substituted polystyrene ( T d10% 296 °C, T g 19 °C). The increased thermal stability of the newly synthesized polymer is hypothesized to arise from the lack of terminal CF3 moieties. The cyclic perfluoroalkylene-substituted polystyrene exhibited hydro- and oleo-phobicities comparable to those of the n -C4 F9 -substituted polystyrene, suggesting that the introduction of cyclic perfluoroalkylene groups instead of the commonly used Rf groups may have the potential to develop thermo-resistant polymers with hydro- and lipo-phobicity. Thew newly synthesized polymer is suitable for a variety of applications requiring high- T g optical polymeric materials. Graphical abstract: Image 1 Highlights: A cyclic perfluoroalkylene-containing polystyrene derivative was synthesized. The cyclic perfluoroalkylene-containing polymer exhibited high hydro- and oleo-phobicities. The newly synthesized polymer exhibited high thermal stability.